2008
DOI: 10.1080/03004430802352038
|View full text |Cite
|
Sign up to set email alerts
|

Constructing identities: perceptions and experiences of male primary headteachers

Abstract: This article presents research undertaken with male headteachers in early years schools within the UK and explores several influential discourses in relation to male headteachers' identities. The article discusses the ways in which different identities are constructed for headteachers by parents, governors and wider society, and also how a variety of discourses impact on men's professional lives. It seeks to examine themes inherent in headteachers' discourses as they reflect upon their roles and experiences wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 19 publications
0
33
0
Order By: Relevance
“…The proportion of Australian female school elementary principals is now over 50% nationally with some states as high as 60% (ABS, 2011). While many women are proving themselves to be effective and highly regarded school leaders, current research has shown that the idea of the male leader still persists in some school communities, the media and the general public (Jones, 2008).…”
Section: Historical Contextmentioning
confidence: 99%
“…The proportion of Australian female school elementary principals is now over 50% nationally with some states as high as 60% (ABS, 2011). While many women are proving themselves to be effective and highly regarded school leaders, current research has shown that the idea of the male leader still persists in some school communities, the media and the general public (Jones, 2008).…”
Section: Historical Contextmentioning
confidence: 99%
“…Lingard and Douglas (1999) and Jones (2008), for example, maintain that such an approach could create an influx of conservative and uncritical men who may simply reinforce and embed more traditional patterns of gender relations that are strongly heterosexual and macho, and orientated around nuclear families and primarily female carers (Wadsworth, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by controversial claims that single mothers do not rear their sons in appropriate ways (Slattery, 2003), which exacerbate gender debates about parenting competencies by presenting strong and contentious perceptions of women 'as the problem' and 'men as the solution' (Smedley, 1998, p. 158). Through the employment of more men in schools it is, thus, argued that those children, who come from homes where fathers are absent, will have greater access to a 'stable male' (Jones, 2008), or a substitute/surrogate 'dad' who can relate better to pupils, support their development, model positive behaviour, and provide the required level of stability and consistency which, in turn, will result in a rise in standards of academic attainment and behaviour (Beynon, 2002).…”
Section: Male Teachers As 'Replacement Fathers'mentioning
confidence: 99%
See 1 more Smart Citation
“…The women in this study were acutely aware of the dominant societal discourse that leadership is inherently male and recognised that within the public discourse they are constantly measured against characteristics of hegemonic masculinity perceived to be appropriate for the role of headteacher (Jones, 2008). Even though women's exercise of leadership in historical and social and educational contexts has been significant (Collard, 2005;Cranston and Ehrich, 2007) this prevalent discourse may in part be a result of the historical recognition of greater numbers of men in leadership roles (Burns, 1978;Schein, 2001).…”
Section: The Construction Of Leadership As Masculinementioning
confidence: 99%